Community Empowerment through Strengthening Students' Competence through the Production of Eco-Enzymes at Al-Mashum Mardiyah Islamic Boarding School, Cugenang District, Cianjur Regency, West Java - Nulhakim, Lukman; Lubena, Lubena; Marthalia, Lia; Salsabila, Anisa Felisia; Siswanto, Fraditya Hafiz (Unram Journal of Community Service, 2024)
Al-Mashum Mardiyah is an Islamic educational institution located at Jalan Simpang Galudra number 76, Cugenang District, Cianjur Regency, West Java, 79.6 KM from the Faculty of Industrial Technology, Jayabaya University. This pesantren was founded because many children in Galudra Village dropped out of school, illiterate and married at a young age even though Galudara Village is not far from Jakarta. This pesantren has a junior high school, high school and vocational school, where graduates from this pesantren are expected to be experts in religion, science and technology based on the Qur'an. SMK Al- Ma'shum Mardiyah has a curriculum about agrotechnology that has an entrepreneurial spirit. The results of discussions with partners at the pesantren, there are problems regarding the production aspect, where the types of products produced by SMK students are still limited. In this PkM which was carried out on July 22 and August 26-30, partners were taught to produce eco-enzymes. The eco-enzyme is made from vegetable waste collected by vocational students around the school. The benefits of this activity are felt by the community because it can increase the type of production. The material presented was understood by 95% of the participants who attended the training